(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In India, the journey towards cashless economy has started in recent days. In the digitalization of India economy, social media has played a key role. Social media has led to revolutionary changes in the distribution channels of companies and the shopping behaviour of the people